Flying Wing Flight Controller - Kubica, Petr; Koukal, Ondřej (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2020)
The aim of this work is to create a flying wing flight controller based on microcontroller Teensy 3.2 with emphasis on modularity and low price of used components.
Keywords: Flight controller; microcontroller; Teensy 3.2; flying wing; airplane model